Sign in

Sign up

Answered by **Mefunky13**

First pick a letter to sibstitute. (I picked x so I'm solving for x) x-8y=36x-8y+8y=36+8yx=8y+36Now substitue x with 8y+36 in the equation you did not solve for x.-5x+y=15-5(8y+36)+y=15Now solve for y-40y-180+y=15-39y-180=15-39y-180+180=15+180-39y=195(-39y=195)/-39y=-5Now solve for x substituting y with -5 (you may use ether equation)x=8y+36x=8(-5)+36x=-40+36x=-4Check:x-8y=36(-4)-8(-5)=36-4+40=3636=36and-5x+y=15-5(-4)+(-5)=1520-5=1515=15

Answered by **tomek1172**

Didn't find the right answer?

Use site search If you are not satisfied with the answer. Or browse Mathematics category to find out more.

Ask Your Question

Questions without answers